Postgraduate taught portfolio review – the cluster approach, non-subject-based grouping of courses and relevant performance indicators - Konstantinidis-Pereira, Alicja (Perspectives (Association of University Administrators (U.K.)), 2018)
This paper summarises a new method of grouping postgraduate taught (PGT) courses introduced at Oxford Brookes University as a part of a Portfolio Review. Instead of classifying courses by subject, the new cluster approach uses statistical methods to group the courses based on factors including flexibility of study options, level of specialisation, research links, vocational character and undergraduate continuity. The model of five defined clusters helps understand an increasing diversity of PGT provision better, find similarities outside of traditional subject divisions and share a good practice outside of the departmental structure of the University. It can assist with a new approach to University-wide marketing activities as well as with evaluation of performance taking into account course specifics within the clusters. The paper proposes a set of new and tailored performance indicators for PGT courses.